Adam and Eve in Romans 1.18–25 and the Greek Life of Adam and Eve - Levison, John R. (New Testament studies, 2004)
This study identifies several dimensions of the Greek Life of Adam and Eve that provide fresh points of entry to Paul's thought in Rom 1.18–25. Principal among these are the suppression of truth, the advent of divine anger, the onset of death, and, most notably, two related exchanges – God's glory for mortality and natural dominion for unnatural subservience to animals. While such features do not specifically characterize Gen 1–3, they belong to a shared conception of the drama of human sin that characterizes and unites both Rom 1 and the Greek Life of Adam and Eve.